The Demand for Programmable Payments - Charles M. Kahn; Maarten R.C. van Oordt (Tinbergen Institute, 2022)
his paper studies the desirability of programmable payments where transfers are automatically executed conditional upon preset objective criteria. We do so by studying optimal payment arrangements in a framework that captures a wide range of economic relationships between two parties. Our framework stacks the cards in favor of programmable payments by considering an environment without legal recourse. The results show that the optimal payment arrangements for long-term economic relationships consist predominantly of simple direct payments. Direct payments increase the surplus by avoiding the liquidity cost of locking-up funds from the moment where the payer commits the funds in a programmable payment until the moment where the conditions are satisfied to release those funds to the payee. Programmable payments will be desirable, and may in fact be the only viable payment arrangement, in situations where economic relationships are of a short duration. Our results identifies a limit to the growth in the demand for payments as their cost decreases: While the number of feasible trading relationships will increase, existing trading relationships will optimally rely on fewer payments.
Keywords: E40; E42; E58; 330; Bill Payments; Blockchain; CBDC; Smart Contracts; Payment Economics